2010
DOI: 10.2214/ajr.09.4081
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Upgrade Rates, and Characteristics of High-Risk Lesions Initially Identified With Breast MRI

Abstract: There are no specific imaging features that predict upgrade for high-risk lesions when detected with MRI. Therefore, surgical excision is recommended because upgrade to invasive carcinoma or ductal carcinoma in situ can occur in up to 31% of cases, regardless of biopsy technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 43 publications
4
30
1
Order By: Relevance
“…6 This finding supports the hypothesis proposed by Liberman et al 15 that the greater rate of underestimation of malignancy in lesions containing ADH biopsied with MRI guidance compared with stereotactic guidance might be related to the greater probability of breast cancer in high-risk women undergoing breast MRI.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…6 This finding supports the hypothesis proposed by Liberman et al 15 that the greater rate of underestimation of malignancy in lesions containing ADH biopsied with MRI guidance compared with stereotactic guidance might be related to the greater probability of breast cancer in high-risk women undergoing breast MRI.…”
Section: Discussionsupporting
confidence: 89%
“…A part of the smaller sample size resulted from a lack of surgical follow-up in 10 cases and inability to correlate the excision site with the biopsy site in 11 cases. A similar limitation was noted in the study by Strigel et al, 6 in which a correlation between the biopsy and surgical excisions sites was unavailable in 22 of 61 (36%) of high-risk lesions detected by MRI biopsy. In cases in which no surgery was performed, the analysis by Menes et al 5 of the Breast Cancer Surveillance Consortium suggested that surgeons are successful at selecting which patients will be suitable for observation with low rates of subsequent breast cancer and suggested, therefore, that management of these high-risk lesions could be determined on a case-by-case basis.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The atypical ductal hyperplasia (ADH) upgrade rate at surgery is reportedly 25-38% (19,30,38,40,42,43). In ductal carcinoma in situ (DCIS), the upgrade rate ranges from 5-24% (19,30,38,44).…”
Section: Radiologic-pathologic Correlationmentioning
confidence: 99%